A NEW VISUALIZATION TECHNIQUE FOR THE STUDY OF SOLUTE DISPERSION IN MODEL POROUS MEDIA - Theodoropoulou M.A.; Karoutsos V.; Kaspiris C.; Tsakiroglou C.D. (My University, 2003)
A new technique of high resolution is developed to perform visualization experiments of the hydrodynamic dispersion of pollutants in transparent glass-etched pore networks, which are regarded as representative models of natural porous media and single fractures. The technique is based on the continuous detection of the sharp colour changes caused on an aqueous solution, as the solute concentration varies, because of the strong sensitivity of a system of indicators to pH. Image analysis is used for the transformation of the spatial distribution of colour intensity to solute concentration profiles. Unidirectional miscible displacement and single source-solute transport experiments are used to identify and quantify the transient and steady-state solute dispersion regimes in a pore network, and estimate the longitudinal and transverse dispersion coefficients as functions of Peclet number. The dispersion coefficients are estimated by fitting the spatial/temporal distribution of solute concentration over various regions of the network to analytic solutions of the convection-dispersion equation, obtained by using a flux-type boundary condition at solute sources. The experimental technique and the method of analysis of its results may be proved very useful for model validation, sensitivity analysis of dispersion coefficients with respect to pore space parameters, and identification of liquid pollutant dispersion regimes in underground aquifers.
Keywords: PORE NETWORK; DISPERSION COEFFICIENTS; PECLET NUMBER; PARAMETER ESTIMATION; IMAGE ANALYSIS; SOLUTE DISPERSION